Surface display of recombinant Drosophila melanogaster acetylcholinesterase for detection of organic phosphorus and carbamate pesticides. - Jingquan Li (PLoS ONE, 2013)
Acetylcholinesterase (AChE) is commonly used for the detection of organophosphate (OP) and carbamate (CB) insecticides. However, the cost of this commercially available enzyme is high, making high-throughput insecticide detection improbable. In this study we constructed a new AChE yeast expression system in Saccharomyces cerevisiae for the expression of a highly reactive recombinant AChE originating from Drosophila melanogaster (DmAChE). Specifically, the coding sequence of DmAChE was fused with the 3'-terminal half of an α-agglutinin anchor region, along with an antigen tag for the detection of the recombinant protein. The target sequence was cloned into the yeast expression vector pYes-DEST52, and the signal peptide sequence was replaced with a glucoamylase secretion region for induced expression. The resultant engineered vector was transformed into S. cerevisiae. DmAChE was expressed and displayed on the cell surface after galactose induction. Our results showed that the recombinant protein displayed activity comparable to the commercial enzyme. We also detected different types of OP and CB insecticides through enzyme inhibition assays, with the expressed DmAChE showing high sensitivity. These results show the construction of a new yeast expression system for DmAChE, which can subsequently be used for detecting OP and CB insecticides with reduced economic costs.